Variation in body size and morphometric traits of males and females of the wall gecko, Tarentola delalandii (Phyllodactylidae) from different environments on Tenerife. Issue 2 (2nd July 2016) - de Fuentes-Fernández, María; Mercedes Suárez-Rancel, María; Molina-Borja, Miguel
Abstract: We analysed sexual dimorphism in body size and several other morphological traits of two populations of Tarentola delalandii on the island of Tenerife (San Cristóbal de La Laguna in the North, and Granadilla de Abona in the South), whose habitats differ in climate and vegetation cover. Sexual size dimorphism was invariant between populations. Males had significantly larger body size (snout−vent length, SVL) than females and SVL was larger in the northern population than in the southern population. Applying a Permutational MANCOVA to the other morphological variables, considering separately head and trunk lengths as covariates, we found a significant effect of population and gender. For the majority of morphological variables (body mass, SVL, width, length and height of the head, trunk length, forelimb and hindlimb, height and width of the tail) studied (eight in each analysis), there were significant differences, males having larger values than females and northern individuals larger values than those of the southern population. Therefore, we confirmed quantitatively a significant male biased sexual dimorphism in body size in the two populations and have shown sexual dimorphism in the characteristics mentioned previously. However, most of the shape-adjusted traits were significantly larger in females than in males. Results are discussed of possible evolutionary, ontogenetic and ecological factors affecting the expression of sexual dimorphism in the species studied.